2- Resolva: a) |x + 3| = 6 * 5 pontos {-3 ; 9} {3 ; 9} {3 ; -9} b) |2x – 6| = x + 2 * 5 pontos {8 ; -4/3} {8 ; 4/3} {-8 ; 4/3} c) |2x – 1| = |-x + 5| * 5 pontos {2 ; -4} {-2 ; -4} {2 ; 4} d) |x² – x – 4| = 2 * 5 pontos {-2 ; -3} {-2 ; 3} {2 ; -3} e) | x+3 | = 7 * 5 pontos {-4 ; -10} {-4 ; 10} {4 ; -10} f) |3x-8 | = 13 * 5 pontos {7 ; -5/3} {-7 ; 5/3} {7 ; 5/3}
luiswarmling:
nao preciso dos calculos!
Soluções para a tarefa
Respondido por
1
Explicação passo-a-passo:
a)
|x + 3| = 6
• x + 3 = 6
x = 6 - 3
x = 3
• x + 3 = -6
x = -6 - 3
x = -9
S = {3, -9}
b)
|2x - 6| = x + 2
• 2x - 6 = x + 2
2x - x = 2 + 6
x = 8
• 2x - 6 = -x - 2
2x + x = -2 + 6
3x = 4
x = 4/3
S = {8, 4/3}
c)
|2x - 1| = |-x + 5|
• 2x - 1 = -x + 5
2x + x = 5 + 1
3x = 6
x = 6/3
x = 2
• 2x - 1 = x - 5
2x - x = -5 + 1
x = -4
S = {2, -4}
d)
|x² - x - 4| = 2
• x² - x - 4 = 2
x² - x - 4 - 2 = 0
x² - x - 6 = 0
Δ = (-1)² - 4.1.(-6)
Δ = 1 + 24
Δ = 25
x = (1 ± √25)/2.1 = (1 ± 5)/2
• x' = (1 + 5)/2 = 6/2 = 3
• x" = (1 - 5)/2 = -4/2 = -2
S = {-2, 3}
e)
|x + 3| = 7
• x + 3 = 7
x = 7 - 3
x = 4
• x + 3 = -7
x = -7 - 3
x = -10
S = {4, -10}
f)
|3x - 8| = 13
• 3x - 8 = 13
3x = 13 + 8
3x = 21
x = 21/3
x = 7
• 3x - 8 = -13
3x = -13 + 8
3x = -5
x = -5/3
S = {7, -5/3}
Perguntas interessantes